2015
DOI: 10.1002/ajmg.a.37293
|View full text |Cite
|
Sign up to set email alerts
|

Paternal uniparental disomy chromosome 14‐like syndrome due a maternal de novo 160 kb deletion at the 14q32.2 region not encompassing the IG‐ and the MEG3‐DMRs: Patient report and genotype–phenotype correlation

Abstract: The human chromosome 14q32 carries a cluster of imprinted genes which include the paternally expressed genes (PEGs) DLK1 and RTL1, as well as the maternally expressed genes (MEGs) MEG3, RTL1as, and MEG8. PEGs and MEGs expression at the 14q32.2-imprinted region are regulated by two differentially methylated regions (DMRs): the IG-DMR and the MEG3-DMR, which are respectively methylated on the paternal and unmethylated on the maternal chromosome 14 in most cells. Genetic and epigenetic abnormalities affecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…While preparing this manuscript, three additional microdeletions were reported that did not include the DMRs, like in our family A. 16,17 As visualized in Figure 3, there is no smallest region of overlap common to all 13 microdeletions. It is therefore likely that several regulatory mechanisms can be disrupted at different positions within the 14q32.2 chromosomal region with a similar clinical outcome.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…While preparing this manuscript, three additional microdeletions were reported that did not include the DMRs, like in our family A. 16,17 As visualized in Figure 3, there is no smallest region of overlap common to all 13 microdeletions. It is therefore likely that several regulatory mechanisms can be disrupted at different positions within the 14q32.2 chromosomal region with a similar clinical outcome.…”
Section: Discussionmentioning
confidence: 82%
“…To our knowledge, 13 patients with a UPD (14)pat phenotype caused by a maternal 14q32 deletion have been reported. [3][4][5]16,17 The precise localization of these is depicted in Figure 3. The clinical characteristics of all deletion carriers, including the cases described here are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these last deleterious effects have been found to be more frequently related to the LRPPRC A354V founder mutation, responsible for an increased mitochondrial vulnerability and nutrient-induced cytotoxicity [ 12 ]. Moreover, different dose effects could also result from functional differences in gene expression depending on the parental origin of the single mutation, as recently described in other neurodevelopmental disorders [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, TS14 has been identified in 58 patients, including 10 patients with epimutations of the IG-DMR and the MEG3 -DMR, and KOS14 has been identified in 57 patients, including 7 patients with epimutations of the two DMRs. 1,2,6,7,8,9 Thus, we examined MLIDs in TS14 and KOS14 caused by epimutations.…”
Section: Introductionmentioning
confidence: 99%